Toughening epoxy with lignin-based additive - Goh, Sally Hwee Li (2014)
This Final Year Project aims to transform a waste by-product Lignin into a viable additive for toughening of epoxy. The chemical structure of AL-COOH was characterized by FTIR and 1NHMR to ensure that the modification is successful. AL-COOH is covalently incorporated into an anhydride-cured epoxy matrix by a one-pot method. After which, more tests were put in place to investigate the rheological properties, thermal stability, curing behavior, microstructure as well as mechanical properties of epoxy to study the impact of the toughening additive on the performance of epoxy. However the main focus of the report is placed on the investigation of thermal and mechanical properties. Incorporation of 1.0wt% of AL-COOH produces the best results out of the different compositions of AL-COOH. The critical stress intensity factor (KIC) and the critical strain energy release rate (GIC) increased by 68% and 164%, proving to be a notable improvement in the fracture toughness as compared to neat epoxy. The improvement in fracture toughness was due to the decreased in cross-linking density and increase in free volume when AL-COOH was incorporated into epoxy matrix.